Comparison of the Potential of Mangrove Forests as an Estimate of Carbon Stocks : A Review - Zahro, Shofiyyatuz; Chika, Syifara (Biocaster : Jurnal Kajian Biologi, 2024)
Global warming is an increase in carbon dioxide gas (CO2) and other gases in the earth's atmosphere, which will make the earth's atmosphere retain more heat coming from the sun. This study aimed to determine the highest carbon stock ratio from various areas with mangrove forest areas. This research was conducted using the grid route method by collecting data from a literature study from different locations in the mangrove forest. The research results obtained that the highest average carbon stock in various regions of Indonesia which has the highest mangrove forest conservation is the Mangrove Area in Pasar Banggi Rembang Village of 737.2 tons/ha with three stations whose species names consist of Rhizophora apiculata, Rhizophora stylosa, and Rhizophora mucronata. High and low carbon content, density, and mangrove species in mangrove leaf litter were influenced by the rate of litter production. This production rate will later affect the high low carbon content in mangrove leaf litter.